How Therapy With Victims of Political Trauma Repairs the Third—Commentary on Gómez and Kovalskys's Work in the Context of Postdictatorship Chile. Issue 1 (2nd January 2018) - Benjamin, Jessica
Abstract : In this discussion I use the concept of the moral Third to designate the position in which we experience the world as lawful because repair is possible. Repair takes place through acknowledgment of harming and consequent suffering. This form of acknowledgment, coupled with social recognition, is considered by the authors to be a crucial part of the therapeutic work with victims of collective trauma, especially of torture by the Pinochet security police. In relation to Gómez's case, I discuss how the moral Third, the representation of a lawful world, is shattered by attacks on the victim's family. Further, the witnessing function is reversed and perverted in torture, where the torturer presents a blank face and denies the very suffering he is inducing. The experience of betrayal becomes the core issue which the therapist seeks to address through the attachment relationship itself. In relation to Kovalskys' case I consider how the moral Third of the activists, the belief in the possibility of a world in which all can live, is attacked in order to affirm the paranoid view that "only one can live." The lived experience of this traumatizing attack is that the child becomes imbued with the sense of not deserving life, of having gained life at the expense of the other. Helping the patient to testify publicly to her personal history and truth becomes part of the healing process in the context of collective trauma.